Pengaruh Pemahaman Akuntansi Zakat dan Tingkat Religiusitas Terhadap Kesadaran Membayar Zakat Pada Pelaku Usaha Kecil dan Menengah (UKM) Muslim di Kota Medan - Ginting, Yuni (Journal Research of Economic and Bussiness, 2024)
Zakat is one of the pillars of Islam that must be fulfilled, there is an obligation and compulsion from Allah SWT for Muslims who have assets exceeding the nisab and have reached the haul, apart from that the potential for zakat is very large, but there are still many muzakki who only remember zakat fitrah but forget the importance of zakat mal. This phenomenon is very interesting to study to see the understanding of zakat accounting and the level of religiosity of business actors towards awareness of paying zakat. This research was conducted by taking a sample of 55 respondents, namely Muslim UKM in Medan City. This research uses a questionnaire as a data collection tool. Structural Equation Modeling - Partial Least Squares (SEM-PLS) was used to analyze the data, so that it could show research results where there was no influence of understanding of zakat accounting and level of religiosity on awareness of paying zakat.